Afterword. On Enlightenment and the Most Difficult Problem of the Human Species - Scott Johnston, James (Con-Textos Kantianos. International Journal of Philosophy, 2015)
In this Afterword, I discuss the papers contained in the dossier in regards to a central issue for Kant: leadership. The issue for Kant is the paradox of the human species’ need for a master that is human yet morally perfect. This of course is an as-yet unobtainable requirement that Kant thinks can only be properly met through a civil constitution. The issues of elitism and the tension between a ‘maximal’ and ‘minimal’ Enlightenment in light of Kant’s requirement will be discussed.